Tropical shrub forage in fattening guinea pigs (Cavia porcellus Linnaeus) - Sánchez Laiño, Adolfo Rodolfo (2017)
The research was carried out in the "La María" Experimental Farm, owned by the State Technical University of Quevedo (UTEQ), located at km 71/2 of Vía Quevedo-Mocache, province of Los Ríos, whose geographic location of 1º5'13"south latitude and 79º32'22" west longitude and at a height of 73 masl. The productive behavior of guinea pigs (Cavia porcellus L.) was determined under the eﬀect of the consumption of tropical bush forages (Morera: Morus alba, Caraca: Erythrina poeppigiana, Golden button: Tithonia diversifolia) and the proﬁtability of the treatments. A completely randomized design (DCA) with ﬁve repetitions was applied. We used 40 male coats of 25 days of age with an average weight of 368.75±36.90 g. To establish the diﬀerences between means, the Tukey test (P≤0.05) was applied. The forage intake (CF), ﬁnal weight (PF), weight gain (GP), feed conversion index (ICA), yield to the carcass (RC) were evaluated. The proﬁtability was determined through the beneﬁt-cost ratio. The highest (P<0.05) total forage consumption was recorded by treatments based on savoy  grass and gold button (1086.80±18.08 and 1116.80±33.34 g, respectively). The highest GP (464.90±34.24 and 438.80±32.20, which represents a gain of 8.30 and 7.84 g animal-1 day-1), ICA  (3.47±0.18 -  3.64±0.22); RC (70.90±0.75 - 68.13±0.74  %), the treatments were based on mulberry and caraca (P<0.05), likewise the most eﬃcient proﬁtability (67.18 - 67.23 %), which shows the positive eﬀect of the inclusion of these forages in the fattening of guinea pigs.